Molecular Line Emission as a Tool for Galaxy Observations (LEGO) - Kauffmann, Jens; Goldsmith, Paul F.; Melnick, Gary; Tolls, Volker; Guzman, Andres; Menten, Karl M. (Astronomy and astrophysics (Berlin), 2017)
Trends observed in galaxies, such as the Gao & Solomon relation, suggest a linear relationship between the star formation rate and the mass of dense gas available for star formation. Validation of such trends requires the establishment of reliable methods to trace the dense gas in galaxies. One frequent assumption is that the HCN (J = 1–0) transition is unambiguously associated with gas at H2 densities ≫ 104 cm-3. If so, the mass of gas at densities ≫ 104 cm-3 could be inferred from the luminosity of this emission line, LHCN (1–0). Here we use observations of the Orion A molecular cloud to show that the HCN (J = 1–0) line traces much lower densities ~ 103 cm-3 in cold sections of this molecular cloud, corresponding to visual extinctions AV ≈ 6 mag. We also find that cold and dense gas in a cloud like Orion produces too little HCN emission to explain LHCN (1–0) in star forming galaxies, suggesting that galaxies might contain a hitherto unknown source of HCN emission. In our sample of molecules observed at frequencies near 100 GHz (also including 12CO, 13CO, C18O, CN, and CCH), N2H+ is the only species clearly associated with relatively dense gas.